HYBRID HARMONY: A PRACTICAL GUIDE TO MANAGING PERFORMANCE AND CULTURE IN A DISTRIBUTED TEAM - Dhenny Asmarazisa; Deri Tiodora; Ramon Zamora (RADJA PUBLIKA, 2026)
The rapid shift to hybrid and distributed work models presents a critical challenge: maintaining cohesive organizational culture and high performance without a shared physical space. This study aims to provide a practical framework for leaders to effectively synchronize performance management with cultural stewardship in a dispersed environment. The methodology involved a qualitative multi-case study analysis of six technology firms that successfully navigated the transition to a hybrid model, supplemented by surveys of 150 team leaders. The results identify five key pillars for success: redefined communication rituals, outcome-based performance metrics, equitable inclusion practices, intentional cultural artifacts, and leadership training for distributed empathy. The discussion argues that performance and culture are mutually reinforcing systems in a hybrid context, not separate domains. It emphasizes that